Mediating autonomy: an essential care practice in mental health - Virginia Faria Damásio Dutra; Hercules Rigoni Bossato; Rosane Mara Pontes de Oliveira (Universidade Federal do Rio de Janeiro, 2017)
ABSTRACT Objectives: Identify psychiatric nursing practices in the mediation of autonomy for social individuals compromised by their psychiatric history, and analyze psychiatric nursing practices focused on the autonomy of individuals who attend a type III psychosocial care center. Methods: Convergent-care research using observation and semi-structured interviews with seven RN nurses from a psychosocial care center and four educational groups in the year 2013. Data analysis used social constructivism as its foundation. Results: Autonomy is presented as a care action that enables users to be the protagonists of their own lives, recognizing their limits and possibilities. Even with mental conditions, patients' potentialities must be recognized. Conclusion: Nurses invest in autonomy and liberty as foundations of care to be stimulated, mediated, or negotiated. Implications for practice: The inclusion of "autonomy mediating" as a care action for patients is emphasized.